2007
DOI: 10.1016/j.neuro.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Autism: Maternally derived antibodies specific for fetal brain proteins

Abstract: Autism is a profound disorder of neurodevelopment with poorly understood biological origins. A potential role for maternal autoantibodies in the etiology of some cases of autism has been proposed in previous studies To investigate this hypothesis, maternal plasma antibodies against human fetal and adult brain proteins were analyzed by western blot in 61 mothers of children with autistic disorder and 102 controls matched for maternal age and birth year (62 mothers of typically developing children (TD) and 40 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
217
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(229 citation statements)
references
References 29 publications
9
217
0
3
Order By: Relevance
“…On the basis of results reported from evaluations of specimens obtained after the child's diagnosis (18)(19)(20), we elected to begin the search for maternal biologic markers by focusing on autoantibodies to human fetal brain proteins measured in mid-pregnancy peripheral blood. With modest sample size for this first study, we found that the frequency of specific bands and band patterns differed some-what by study group and by autism onset type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of results reported from evaluations of specimens obtained after the child's diagnosis (18)(19)(20), we elected to begin the search for maternal biologic markers by focusing on autoantibodies to human fetal brain proteins measured in mid-pregnancy peripheral blood. With modest sample size for this first study, we found that the frequency of specific bands and band patterns differed some-what by study group and by autism onset type.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated that immunoreactivity persisted in maternal circulation for up to 18 years after delivery. Finally, we recently reported that autoantibodies to human fetal brain proteins at 37 kDa and 73 kDa were significantly more often present in the plasma of mothers of children with autism compared with control mothers (20). In that study, maternal plasma was collected on average 3.5 years after the birth of the study child.…”
mentioning
confidence: 99%
“…The maternal transfer of autoantibodies from the mother to child during pregnancy is well documented, and is associated with a number of factors that can affect both pregnancy and neonatal outcome. 11 The presence of autoantibodies directed against critical neuronal components of fetal brain extracts in a subset of mothers of ASD children provides supporting evidence that one potential mechanism linking maternal immune components with ASD involves the transfer of autoantibodies from mother to the developing fetus during pregnancy 15,16,17,20 (Table 2).…”
Section: Maternal Antibodiesmentioning
confidence: 91%
“…Future studies will need to better characterize the behavioral changes evoked by these antibodies and their relevance to core features or symptoms of ASD, as well as the potential cellular targets of these antibodies. Although the frequency at which potential autoantibodies are present in mothers who have children with ASD is low, the significance of carrying these antibodies may be substantial 16 and presents an exciting avenue for screening and therapy.…”
Section: Maternal Antibodiesmentioning
confidence: 99%
“…Anti-fetal antibodies can pass the blood-brain barrier which is not fully developed during the prenatal period [73]. Braunschweig et al identified that anti-fetal brain antibodies, IgG, were found in ~11.5% of mothers of children with ASD, but not in mothers of children of typical development and mothers of children with development delay [74]. Injections of IgG collected from mothers of children with ASD into pregnant rhesus monkeys during the first and second trimesters led to altered brain volume and social behavior development in the offspring [75].…”
Section: Immune Dysregulation In Asdmentioning
confidence: 99%